1995
DOI: 10.1093/rfs/8.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Rational Prepayment and the Valuation of Mortgage-Backed Securities

Abstract: This article presents a new model of mortgage prepayments, based on rational decisions by mortgage holders. These mortgage bolders face beterogeneous transaction costs, which are explicitly modeled. The model is estimated using a version of Hansen's (1982) generalized method of moments, and is sbown to capture many of the empirical features of mortgage prepayment. Estimation results indicate that mortgage holders act as tbougb tbey face transaction costs tbat far exceed tbe explicit Costs usually incurred on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
265
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(272 citation statements)
references
References 14 publications
(15 reference statements)
7
265
0
Order By: Relevance
“…However, the empirical literature has shown that, even when conditioning on observable mortgage characteristics and property characteristics, there is substantial heterogeneity in default behavior across borrowers. 23 A common explanation of this finding, advocated in the literature (see Stanton, 1995, for example), is that significant transactions costs are associated with defaulting, and these transactions costs differ across borrowers. As discussed above, these costs may include moving costs, default penalties that take the form of limited future access to credit markets, sentimental attachment to the home, or even the presence of moral qualms associated with defaulting on one's debts.…”
Section: Results From the Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the empirical literature has shown that, even when conditioning on observable mortgage characteristics and property characteristics, there is substantial heterogeneity in default behavior across borrowers. 23 A common explanation of this finding, advocated in the literature (see Stanton, 1995, for example), is that significant transactions costs are associated with defaulting, and these transactions costs differ across borrowers. As discussed above, these costs may include moving costs, default penalties that take the form of limited future access to credit markets, sentimental attachment to the home, or even the presence of moral qualms associated with defaulting on one's debts.…”
Section: Results From the Modelmentioning
confidence: 99%
“…19 Stanton (1995) was the first study to incorporate transactions costs into a model of mortgage termination. 20 Kau, Keenan, and Kim (1994) make this point in the context of an option-theoretic model.…”
Section: Results From the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…They require about 10% of decrease on their monthly mortgage payments (if we compute these "savings" implied by 1% mortgage rate decrease) to refinance and they do not prepay for exogenous reasons. This specification is somewhat similar to the specification of the prepayment in [10], where the prepayment rate, however, was assumed to be governed by the borrower's liability (the so called option-based approach).…”
Section: Numerical Examplementioning
confidence: 99%